Analisis Kepuasan Pelanggan Terhadap Usaha Kuliner Dimsum Online - Akbar, Y Rahmat; Mar'aini; Asneldy, Muhammad Farel; Febrianti, Priska Emilia; Putri, Shinta Aulia (Jurnal Pustaka Manajemen (Pusat Akses Kajian Manajemen), 2025)
The development of digital technology has driven the growth of online-based culinary businesses, including in the city of Pekanbaru. One of the players in this field is O Dimsum Pekanbaru, which utilizes social media to market its products without having a physical outlet. This study aims to analyze customer satisfaction levels toward O Dimsum’s products and services, as well as identify the factors that influence them. The research method used is a descriptive qualitative approach, with data collected through interviews with customers who have made purchases more than twice. The results show that, in general, customers are satisfied with the taste of the products, consistency of quality, reasonable pricing, as well as the speed and friendliness of the admin service during the ordering process. The hygienic and attractive packaging, along with effective promotion through Instagram, also contributes to strengthening customer satisfaction. However, there are some notes regarding delivery delays during peak hours, which require attention for future service improvements.